2017
DOI: 10.3389/fcimb.2017.00375
|View full text |Cite
|
Sign up to set email alerts
|

Ixodes scapularis Tick Cells Control Anaplasma phagocytophilum Infection by Increasing the Synthesis of Phosphoenolpyruvate from Tyrosine

Abstract: The obligate intracellular pathogen, Anaplasma phagocytophilum, is the causative agent of life-threatening diseases in humans and animals. A. phagocytophilum is an emerging tick-borne pathogen in the United States, Europe, Africa and Asia, with increasing numbers of infected people and animals every year. It is increasingly recognized that intracellular pathogens modify host cell metabolic pathways to increase infection and transmission in both vertebrate and invertebrate hosts. Recent reports have shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 57 publications
(131 reference statements)
1
34
0
Order By: Relevance
“…Genome analysis of many rickettsial pathogens has reported absence of alanine and glutamate synthesis pathways (Dunning Hotopp et al, 2006). However, in I. scapularis, all genes required for the synthesis of glutamate and alanine from alpha-ketoglutarate and pyruvate, respectively, are present (Cabezas-Cruz, Espinosa, et al, 2017). Studies have shown that A. phagocytophilum decreases glutamate and alanine levels upon infection in ticks (Cabezas-Cruz, Espinosa, et al, 2017;Villar et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Genome analysis of many rickettsial pathogens has reported absence of alanine and glutamate synthesis pathways (Dunning Hotopp et al, 2006). However, in I. scapularis, all genes required for the synthesis of glutamate and alanine from alpha-ketoglutarate and pyruvate, respectively, are present (Cabezas-Cruz, Espinosa, et al, 2017). Studies have shown that A. phagocytophilum decreases glutamate and alanine levels upon infection in ticks (Cabezas-Cruz, Espinosa, et al, 2017;Villar et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In our proteomics analysis, this 69.5 kDa protein was found over-represented in response to feeding stimulus alone (Proteomics: NIF/NINF = 0.30; Western blot: NIF/NINF = 99915.597/ND) and also in response to infection (Proteomics: INF/NINF = 0.38; Western blot: INF/NINF = 9234.421/ND) (Supplementary Table S1, Figure 6A). This positive regulation suggests a role of PCCA enzyme as a key for energy supply, maybe through the formation of building blocks or nutrients that ultimately contributes to tick and parasite growth [21]. Moreover, previous studies reported that bacteria and fungi metabolize and detoxify propionyl-CoA by the 2-methylcitrate cycle [87] to overcome its toxicity and growth inhibition properties [88].…”
Section: New Insights About An Uncharacterized Proteinmentioning
confidence: 90%
“…According to the defined criteria for target selection for RNA interference studies, in silico analysis were performed revealing characteristics such as the putative function, subcellular localization, and immunogenicity of these proteins. STRING analysis showed that those targets and their network are linked to ubiquitination and metabolic pathways (Supplementary Figure S4), essential for tick fitness [21,74] and described as drug targets in other contexts [75,76]. CELLO, TMHMM, and SignalP servers predicted the cytoplasmatic localization and absence of transmembrane helices or signal peptides in both proteins, that alongside with their antigenic propensity (UB2N: 1.0357, with 8 antigenic determinants; PCCA: 1.0357, with 28 antigenic determinants) indicate that those proteins could be tested to evaluate their potential as protective antigens.…”
Section: R Bursa Cellular Machinery In Response To Feeding and Infecmentioning
confidence: 99%
See 2 more Smart Citations